2017
DOI: 10.1371/journal.pntd.0005725
|View full text |Cite
|
Sign up to set email alerts
|

Uniform multidrug therapy for leprosy patients in Brazil (U-MDT/CT-BR): Results of an open label, randomized and controlled clinical trial, among multibacillary patients

Abstract: BackgroundLeprosy control is based on early diagnosis and multidrug therapy. For treatment purposes, leprosy patients can be classified as paucibacillary (PB) or multibacillary (MB), according to the number of skin lesions. Studies regarding a uniform treatment regimen (U-MDT) for all leprosy patients have been encouraged by the WHO, rendering disease classification unnecessary.Methodology and findingsAn independent, randomized, controlled clinical trial conducted from 2007 to 2015 in Brazil, compared main out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 19 publications
0
50
0
9
Order By: Relevance
“…The decision was taken based in only one study [27] which, although it shows an interesting design, its non-randomized and has a very low quality of evidence [44]. Also, the study has not been valued in comparison with other studies, and besides these, its findings had not been supported by a RCT [35].…”
Section: Main Findingsmentioning
confidence: 99%
“…The decision was taken based in only one study [27] which, although it shows an interesting design, its non-randomized and has a very low quality of evidence [44]. Also, the study has not been valued in comparison with other studies, and besides these, its findings had not been supported by a RCT [35].…”
Section: Main Findingsmentioning
confidence: 99%
“…To this date, there is nothing in short period of time to replace MDT [28]. Recently, the recommendation of the WHO about the implementation of U-MDT among central strategies for leprosy control in the quadrennium 2017/2020 was published [29,30]. In Vietnam, there was no controlled clinical study, comparing the efficacy of U-MDT and WHO-MDT for PB and MB patients.…”
Section: Discussionmentioning
confidence: 99%
“…This was partially due to a break in the paradigm that leprosy patients do not re-infect, since the decoding of the complete genome of M. leprae isolated from patients with a relapse of the disease revealed that the same patient could be infected at different times with different strains of this bacillus 12 . Following the rationale for the treatment of tuberculosis, a new single therapeutic regimen (U-MDT) for leprosy will be adopted in 2018, which includes three drugs, for all patients regardless of clinical classification for a period of only six months 13 .…”
Section: Leprosymentioning
confidence: 99%